Temporal, lithospheric and magmatic process Controls on ni, cu and platinum-group element (PGE) mineralisation: A case study from Scotland - Hughes, Hannah S. R. (2015)
A temporal and spatial relationship between plume magmatism, cratonic lithosphere and the occurrences of orthomagmatic Ni-Cu and platinum-group element (PGE) sulphide mineralisation has been documented in the literature. However the underlying causes for this correlation have yet to be resolved – is there an inherent feature of the cratonic lithosphere and its mantle ‘keel’ that controls mineralisation? Or is this correlation purely a preservational bias in the geological record? Scotland has experienced multiple tectono-magmatic events and provides an ideal testing ground, or ‘framework’, in which to assess the role of lithospheric mantle on chalcophile element (Ni and Cu) and precious metal (PGE and Au) abundances through time. Given the well-documented geological history of the region (including several suites of mantle xenoliths), coupled with exploration campaigns in Greenland (with which Scotland has comparable geology), this thesis aims to assess the contributions and influences of lithospheric mantle vs. asthenospheric mantle during melting and mineralisation. It also evaluates the Ni-Cu-PGE mineralisation potential for Scotland, particularly in a Noril’sk-type conduit-hosted setting within the British Palaeogene Igneous Province (BPIP). The earliest major tectono-magmatic event following cratonisation of the North Atlantic Craton (NAC) occurred c. 2.4 Ga during Palaeoproterozoic extension, forming the maficultramafic Scourie Dyke Swarm. Despite evidence for lithospheric mantle melting at this time, the subcontinental lithospheric mantle (SCLM) below the Scottish portion of the NAC did not become severely depleted in sulphides or PGE. Instead, spinel lherzolite mantle xenoliths from this region (e.g., Loch Roag) record an influx of carbonatite-associated sulphides at this time, enriched in PGE, and providing a deeper indication of continental extension that may be correlated to carbonatitic intrusions in Greenland. Subsequent collision and orogenesis of the NAC in the late Palaeoproterozoic (c. 1.9 to ...